Analysis of the use of virtual reality games for cognitive assessment in older adults: A systematic review (Research, Society and Development, 2025)
Population aging increases the prevalence of cognitive impairments, demanding effective tools for assessment and intervention. This systematic review aimed to analyze the use of Virtual Reality (VR) games for cognitive function assessment in older adults, focusing on reaction time, usability, and acceptance. Searches were conducted in PubMed, Embase, Cochrane Library, Scopus, BVS, SciELO, and LILACS databases without time restrictions, using descriptors related to older adults, virtual reality, and cognitive assessment. After duplicate removal, original articles using VR games for cognitive evaluation and presenting data on reaction time, usability, or acceptance were selected. Six studies were included, involving diverse VR technologies and cognitive variables. Results indicate that VR games are effective in measuring cognitive and motor reaction times and show good usability and engagement among older adults. However, physical discomforts (visual fatigue, nausea) and difficulties adapting to technology were reported. It is concluded that VR is a promising tool for cognitive assessment in older adults, provided that devices and interfaces are adapted to population limitations, ensuring safety, usability, and acceptance.